Komunikasi Dakwah Penyuluh Agama Islam Dalam Merespons Tantangan Modernisasi: Studi di Masjid Bait Al-Tawwabin, Desa Krimun Losarang - Hendra Lesmana (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
Modernization creates big challenges for Islamic religious instructors in conveying da'wah amidst social and cultural changes. This research analyzes the da'wah communication strategy at the Bait Al-Tawwabin Mosque, Losarang District, using a qualitative approach through observation, interviews and documentation. The results show that religious instructors utilize digital technology, participatory approaches, and relevant preaching materials to answer the needs of modern society. The challenges faced include limited resources, varying levels of religious understanding, and the influence of popular culture. Innovative communication strategies have been proven to increase congregational participation and religious awareness. This research recommends technology training for religious instructors, collaboration with local communities, and integration of religious moderation values ​​in preaching.